Association between sodium–glucose cotransporter-2 inhibitors and risk of sudden cardiac death or ventricular arrhythmias: a meta-analysis of randomized controlled trials. Issue 1 (1st August 2021) - Sfairopoulos, Dimitrios; Zhang, Nan; Wang, Yueying; Chen, Ziliang; Letsas, Konstantinos P; Tse, Gary; Li, Guangping; Lip, Gregory Y H; Liu, Tong; Korantzopoulos, Panagiotis
Abstract: Aims : Sudden cardiac death (SCD) and ventricular arrhythmias (VAs) are important causes of mortality in patients with type 2 diabetes mellitus (T2DM), heart failure (HF), or chronic kidney disease (CKD). We evaluated the effect of sodium–glucose cotransporter-2 (SGLT2) inhibitors on SCD and VAs in these patients. Methods and results : We performed a systematic review and meta-analysis of randomized controlled trials (RCTs) that enrolled patients with T2DM and/or HF and/or CKD comparing SGLT2i and placebo or active control. PubMed and ClinicalTrials.gov were systematically searched until November 2020. A total of 19 RCTs with 55 , 590 participants were included. Sudden cardiac death events were reported in 9 RCTs (48 patients receiving SGLT2i and 57 placebo subjects). There was no significant association between SGLT2i therapy and SCD [risk ratio (RR) 0.74, 95% confidence interval (CI) 0.50–1.08; P  = 0.12]. Ventricular arrhythmias were reported in 17 RCTs (126 patients receiving SGLT2i and 134 controls). SGLT2i therapy was not associated with a lower risk of VAs (RR 0.84, 95% CI 0.66–1.06; P  = 0.14). Besides the subgroup of low-dosage SGLT2i therapy that demonstrated decreased VAs compared to control (RR 0.45, 95% CI 0.25–0.82; P  = 0.009), or to placebo (RR 0.46, 95% CI 0.25–0.85; P  = 0.01), further subgroup analysis did not demonstrate any significant differences. Conclusion : SGLT2i therapy was not associated with an overall lower risk of SCD or VAs in patients with T2DM and/or HF and/or CKD. However, further research is needed since the number of SCD and VA events were relatively few leading to wide confidence intervals, and the point estimates suggested potential benefits.